Comparative investigation of combustion and thermal characteristics of a conventional micro combustor and micro combustor with internal straight/spiral fins for thermophotovoltaic system. (18th June 2021) - He, Ziqiang; Yan, Yunfei; Li, Xiuquan; Shen, Kaiming; Li, Junnan; Zhang, Zhien
Abstract: The energy output and energy conversion efficiency of MTPV system are relatively low due to the energy loss. In order to improve the energy output of micro-thermophotovoltaic (MTPV) system, the internal straight and spiral fins are introduced into the micro combustor. The impact of hydrogen mass flow rate, equivalence ratio, and materials on the thermal performance are investigated. The increase of hydrogen mass flow rate brings higher average outer wall temperature, but the temperature difference also increases and the temperature uniformity becomes worse. The equivalence ratio of 1 is suggested to obtain higher average outer wall temperature and better temperature uniformity. The materials with higher thermal conductivity can obtain better thermal performance. Meanwhile, the higher thermal conductivity can also reduce the impact of introduction of internal fins. Highlights: The performance of micro combustors with/without straight/spiral fins are compared. The effect of inlet hydrogen mass flow rate is investigated. The impact of equivalence ratio on thermal performance is studied. The impact of solid materials on thermal performance are investigated.